The term problematic in the exacerbation of the relationship between the Region and the Center Pracmatical, Analytical reading - امىدرس امدکخِر شٔروان أًِروجٔد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
Political terminology and designations have a fundamental power in the political battle and political negotiations; therefore, we see that the most political negotiations as confirmed by the French psychologists are failures not only for different doctrines and principles, but also for different meanings of words and various peripheral connotations. Thus, the repercussions of the referendum have left a language charged between the central government and the region; they entered into a new conflict through the instrument of terms and political vocabulary that mimics their goals and justify what they want to reach; this has negatively affected the mechanism of the relationship between the two sides. ; Base it on above, in this paper (The term problematic in the exacerbation of the relationship between the Region and the Center) we will organize this kind of language through political terms, then theorizes and deals the content of this language. So, this language played bad roles between Kurdistan Region Government and Central Government, We will deal it through the live samples in Media between both sides. The important of this study in the new events that happened before referendum and after it, and our studies will be based on pragmatic theory; we hope our studies will be good steps in the political, linguistic and media area.